Mechanism of Ethylene Action: Biological Activity of Deuterated Ethylene and Evidence against Isotopic Exchange and cis-trans-Isomerization - Beyer, Elmo M. (1972)
Deuterated ethylene was used to study the mechanism of ethylene action in etiolated pea seedlings (Pisum sativum L. cv. Alaska). No apparent differences were observed in the biological activity of tetradeuteroethylene (C(2)D(4)) and ordinary ethylene (C(2)H(4)) using the pea stem straight growth assay. The absence of an isotopic effect is discussed in relation to the possibility that ethylene binds to a metal or that carbon to hydrogen bonds of ethylene are broken during its mechanism of action. Analyses by gas chromatography of gas samples obtained from chambers containing intact etiolated pea plants exposed to 2 microliters of C(2)D(4) per liter of air for up to 5 days resulted in no detectable exchange between the deuterium atoms of C(2)D(4) and the hydrogen atoms of the tissue. Similarly, infrared spectra of gas samples obtained from chambers containing plants exposed to either cis or trans-C(2)D(2)H(2) indicated that no conversion had occurred to the corresponding trans or cis isomer. These results suggest that the mechanism of ethylene action does not involve an intermediate ethylene complex resulting in hydrogen exchange or cis-trans isomerization during a possible catalytic activation of the receptor site(s).